PELATIHAN JURNALISTIK BAGI SISWA SEKOLAH MELALUI PENGGUNAAN MEDIA SOSIAL DI ERA MILENIAL - Saptadi, Norbertus Tri Suswanto; Marwi, Hans Christian; Hamdani, Fransiskus Aurelio (LPPM Universitas Nusa Mandiri, 2024)
The dynamics of students in high school currently face various strong and unique challenges related to understanding journalism and the use of social media tools in the millennial era. The use of computers is a real activity of Youth Catholic Community (YCC) which continues to be dynamic. The problems faced by Cenderawasih Catholic High School and Frater High School students in using social media are a lack of good and wise knowledge and understanding, still having an emotional nature or lack of self-control, and not using social media applications constructively. Student learning practices still require serious efforts to increase productivity to be targeted, effective and measurable. The training aims to educate school students in understanding journalistic concepts with 3 (three) main aspects in the use of social media in the millennial era, namely: cognitive (knowledge), affective (attitude), and psychomotor (skills) to produce creative social media content with character constructive. Training methods include pre-training (information questionnaire), training implementation (tutorial, practice, and presentation) and training evaluation (rubric questionnaire). The training has educated students in understanding journalistic concepts with 3 (three) aspects of using social media in the millennial era. The results of the evaluation of 30 students, namely: cognitive aspects of 18 people or 60.00%, affective aspects of 22 people or 73.33%, and psychomotoric aspects of 21 people or 70.00%, so it can be said that in general students have been able to understand the use of social media well good.